Early Childhood Education Based On Local Wisdom: Learning Innovations To Shape Children's Cultural Character - Adim Dwi Putranti (PT. Anagata Sembagi Education, 2025)
Early Childhood Education (PAUD) plays a vital role in shaping the foundation of children's personalities, moral values, and character from an early age. In an era of globalization that poses challenges to cultural identity, integrating local wisdom into the PAUD learning process is an innovative, relevant, and strategic approach. This article discusses how early childhood education based on local wisdom can be an effective means of shaping children's cultural character. This approach emphasizes the importance of promoting local values such as mutual cooperation, mutual respect, love for the environment, and honesty through contextual learning media, such as folk tales, traditional games, regional songs, and cultural practices adapted to the children's age. This research uses a literature review method on various scientific works and educational practice reports in the field, particularly in early childhood education institutions in various regions of Indonesia. The results of the study show that the local wisdom-based learning approach not only increases children's interest in learning but also fosters a love for the homeland, appreciation for diversity, and builds a strong foundation for noble character. Furthermore, family and community involvement in education becomes more intensive through this approach. Therefore, it is important for educators, policymakers, and other stakeholders to encourage the development of an early childhood education curriculum that is adaptive to local values in order to support sustainable and culturally sensitive character education.